2017
DOI: 10.1177/1367006917709094
|View full text |Cite
|
Sign up to set email alerts
|

There are no language switching costs when codeswitching is frequent

Abstract: International audienceAims and Objectives/Purpose/Research QuestionsThere is ongoing discussion as to the cost of language switching, with some studies indicating high cost and others showing low or no cost. The main research question in this paper is whether there are language switching costs in communities in which codeswitching is frequent. Design/Methodology/Approach We conducted two on-line experiments, i.e. a picture choice with sentence auditory stimuli and a word recognition task in sentence context. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 42 publications
5
51
0
Order By: Relevance
“…As research on codeswitching continues to grow, we suggest that more interdisciplinary studies are needed that prioritize the role of experience in language processing. An exciting aspect of recent work is that we are beginning to see more theoretical and empirical developments that take into account the linguistic repertoire (e.g., Adamou and Shen 2017) and the interactional context (e.g., Green and Abutalebi 2013) of speakers. We capitalize on the importance of pairing linguistically informed stimuli with an appropriate bilingual sample and encourage future research to adopt the corpus-to-cognition approach we have described here.…”
Section: Discussionmentioning
confidence: 99%
“…As research on codeswitching continues to grow, we suggest that more interdisciplinary studies are needed that prioritize the role of experience in language processing. An exciting aspect of recent work is that we are beginning to see more theoretical and empirical developments that take into account the linguistic repertoire (e.g., Adamou and Shen 2017) and the interactional context (e.g., Green and Abutalebi 2013) of speakers. We capitalize on the importance of pairing linguistically informed stimuli with an appropriate bilingual sample and encourage future research to adopt the corpus-to-cognition approach we have described here.…”
Section: Discussionmentioning
confidence: 99%
“…Here we put forth the proposal, based on quantitative analyses of spontaneous codeswitched speech, that codeswitching serves as a toolkit, or an opportunistic strategy for optimizing task performance in cooperative communication. While previous research has focused largely on the costs that codeswitching brings to language processing ( Guzzardo Tamargo et al, 2016 ; Adamou and Shen, 2017 ; Beatty-Martínez and Dussias, 2017 ; Byers-Heinlein et al, 2017 ; for reviews see Van Hell et al, 2015 , 2018 ), we consider the possible advantages that codeswitching may offer to language producers during bilingual language interactions. Critical to this endeavor is the view that codeswitching offers a unique flexibility that is driven by an interplay of bottom-up and top-down processes, but through which resources from both languages are ultimately recruited to convey speakers’ communicative intentions.…”
Section: Introductionmentioning
confidence: 99%
“…These frequencies may also shed light to the language switching costs that have been noted in the experimental literature. Recently, Adamou and Shen (2019) and Johns, Valdés Kroff, and Dussias (2018) showed that language switching costs align with the codeswitching habits of the community as documented in corpus studies. The typological scale of language mixing presented in Figure 1 needs to be enriched by other layers of annotation.…”
mentioning
confidence: 90%